Extra corporeal membrane oxygenation in the critical trauma patient. Issue 2 (April 2019) - Della Torre, Valentina; Robba, Chiara; Pelosi, Paolo; Bilotta, Federico
Abstract : Purpose of review: The purpose of this review is to describe recent evidence regarding the use of extracorporeal membrane oxygenation (ECMO) as salvage therapy for severe cardiac or respiratory failure in patients with trauma. The characteristics of this cohort of patients, including the risk of bleeding and the need for systemic anticoagulation, are generally considered as relative contraindications to ECMO treatment. However, recent evidence suggests that the use of ECMO should be taken in consideration even in this group of patients. Recent findings: The recent findings suggest that venous–venous ECMO can be feasible in the treatment of refractory respiratory failure and severe acute respiratory distress syndrome trauma-related. The improvement of ECMO techniques including the introduction of centrifugal pumps and heparin-coated circuits are progressively reducing the amount of heparin required; moreover, the application of heparin-free ECMO showed good outcomes and minimal complications. Venous–arterial ECMO has emerged as a salvage intervention in patients with cardiogenic shock and after cardiac arrest. Venous–arterial ECMO provides circulatory support allowing time for other treatments to promote recovery in presence of acute cardiopulmonary failure. Only poor-quality evidence is available, for venous–arterial ECMO in trauma patients. Summary: ECMO can be considered as a safe rescue therapy even in trauma patients, including neurological injury, chest trauma as well as burns. However, evidence is still poor; further studies are warranted focusing on trauma patients undergoing ECMO, to better clarify the effect on survival, the type and dose of anticoagulation to use, as well as the utility of dedicated multidisciplinary trauma-ECMO units.